PENYIDIKAN HUKUM TERHADAP TINDAK PIDANA PENYELUNDUPAN TELEPON SELULER DI WILAYAH HUKUM BEA DAN CUKAI KABUPATEN SIAK - Risky Ramadhan; Evi Deliana; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Smuggling occurs in many Indonesian customs areas, one of them is the Siak Regency customsarea. The smuggling that took place in the Siak Regency was smuggling mobile phones. Because the customsarea of Siak Regency has many rat ports that are not known by the Siak Customs and Excise officers. Inconnection with the smuggling of cellular telephones, it has been explained in article 33 paragraph 1 of LawNumber 11 of 1995 Concerning excise that the Customs and Excise Official is authorized to take thenecessary actions on goods subject to excise. Regarding the cell phone smuggling case handled by Customsand Excise officials, it starts with the investigation process. The function of the investigation is to find outand determine what events actually happened and in charge of making the minutes and reports that will bethe basis for the beginning of the investigation.This research is a sociological juridical research that is a research conducted by holding legalidentification and how effective the implementation of the law applies in society. This research wasconducted at the Customs and Excise Office in Siak Sri Indrapura Regency. While the population andsample are parties related to the problem examined in this study, the source of the data used, primary data,secondary data, and tertiary data. Data collection techniques in this study were interviews and literaturereview.From the results of the research that the author did can be concluded, first the Legal InvestigationAgainst Cellular Phone Smuggling Acts has not been conducted in accordance with the applicableprovisions as regulated in the Criminal Procedure Code and Law Number 39 Year 2007 Concerning Excise,customs and excise officials have not found cellphone smugglers. this, so that the enforcement of cell phonesmuggling has not been fully erect. The Two Obstacles in Investigation of Cell Phone Smuggling in the SiakCustoms and Excise Legal Territory have two factors. Namely internal and external factors.Keywords: Legal Investigations - Criminal Actions - Smuggling